Consistent genes associated with structural changes in clinical Alzheimer’s disease spectrum - Lu, Yingqi; Zhang, Xiaodong; Hu, Liyu; Cheng, Qinxiu; Zhang, Zhewei; Zhang, Haoran; Xie, Zhuoran; Gao, Yiheng; Cao, Dezhi; Chen, Shangjie; Xu, Jinping (Frontiers in Neuroscience, 2024)
BackgroundPrevious studies have demonstrated widespread brain neurodegeneration in Alzheimer’s disease (AD). However, the neurobiological and pathogenic substrates underlying this structural atrophy across the AD spectrum remain largely understood.MethodsIn this study, we obtained structural MRI data from ADNI datasets, including 83 participants with early-stage cognitive impairments (EMCI), 83 with late-stage mild cognitive impairments (LMCI), 83 with AD, and 83 with normal controls (NC). Our goal was to explore structural atrophy across the full clinical AD spectrum and investigate the genetic mechanism using gene expression data from the Allen Human Brain Atlas.ResultsAs a result, we identified significant volume atrophy in the left thalamus, left cerebellum, and bilateral middle frontal gyrus across the AD spectrum. These structural changes were positively associated with the expression levels of genes such as ABCA7, SORCS1, SORL1, PILRA, PFDN1, PLXNA4, TRIP4, and CD2AP, while they were negatively associated with the expression levels of genes such as CD33, PLCG2, APOE, and ECHDC3 across the clinical AD spectrum. Further gene enrichment analyses revealed that the positively associated genes were mainly involved in the positive regulation of cellular protein localization and the negative regulation of cellular component organization, whereas the negatively associated genes were mainly involved in the positive regulation of iron transport.ConclusionOverall, these results provide a deeper understanding of the biological mechanisms underlying structural changes in prodromal and clinical AD.